A comparative study of program format and presentation methods between top-rated Western and Thai podcasts - Sukittanon, Siwaporn (RMUTSB ACADEMIC JOURNAL (HUMANITIES AND SOCIAL SCIENCES), 2023)
This study compares contents and formats between top-rated Western and Thai podcasts and also suggests popular podcasts’ qualifications. The content analysis was conducted based on the radio program formats, transmedia storytelling, and PodCred Framework. This research purposively selected sixty top-rated Western and Thai podcast samples in October 2021. The results of this study showed that top-rated podcasts shared the following characteristics; having affiliation with organizations or media networks, featuring evergreen content, introducing programs with jingles, and releasing new episodes once a week. The podcast hosts were well-known and conversed fluently at an easy-to-understand speed. Podcasts were delivered in the form of co-hosted talks, interviews, and narrative style. Top-rated podcasts displayed information about the shows’ names, creators, program descriptions, and logos, while episode-level details were less likely to be fully displayed. On average, top-rated Western podcasts lasted longer in business. Popular content genres were different. While news, comedy, and true crimes were popular content in Western, business and education were popular in Thailand. Top-rated podcasts used cross-media storytelling, which involved distributing the same content across various channels. However, Western podcasts also used transmedia storytelling to tell stories and supplement their podcast content with different storylines on websites, Facebook pages, and YouTube.